Modelo não linear para determinação de vida útil de ferramenta de corte na indústria madeireira - Trejo Franco, Jhonattan José (2023)
The main variables that exert the greatest influence on the efficiency of the timber industries, and that are controllable by the production team, are the quality of the products, the loss of raw material, and the productivity of the lines. Knowing the working limit of the cutting tools is especially important, and in most cases, this operation is carried out empirically. In this thesis, a quantitative model is developed that allows defining the work limit or useful life of cutting tools in the timber industry, considering the variability of industrial processes, relating energy consumption during cutting and the specific work performed by the saws, which is defined by the cut length or lumber volume. The developed model provides a non-linear mathematical fit composed of a modeled function with a quasi-logarithmic behavior and an exponential part. The working limit of the cutting tools is determined through differential equations, identifying the inflection point in the function. The theoretical model was experimentally corroborated in a multi-objective way by relating energy consumption during cutting, the surface and dimensional quality of the products, the specific work of the saws, and the wear of the tools. The quantitative model presented an acceptable approximation since by estimating the value of the inflection point it would be possible to know the work limit or useful life of the tools in the wood cutting and, in this way, avoid all the negative consequences in an uncontrolled cutting process.